Brush cytology in the assessment of pancreatico–biliary strictures: a review of 406 cases. Issue 6 (1st June 2001) - Stewart, C J R; Mills, P R; Carter, R; O'Donohue, J; Fullarton, G; Imrie, C W; Murray, W R
Abstract : Aims —To assess the accuracy of brush cytology in patients investigated for pancreatico–biliary strictures. Methods— All pancreatico–biliary brush cytology specimens submitted from two major teaching hospitals over a 6.5 year period were reviewed. Four hundred and forty eight satisfactory specimens from 406 patients with adequate clinical and/or pathological follow up data were examined in the study period. Results —Two hundred and forty six patients (60.6%) were shown to have neoplastic strictures. One hundred and forty seven tumours were identified cytologically, including 87 of 146 pancreatic carcinomas, 29 of 47 cholangiocarcinomas, one of one bile duct adenoma, four of seven carcinomas of the gallbladder, eight of 13 ampullary carcinomas, two of three ampullary adenomas, 10 of 16 malignancies of undetermined origin, none of two islet cell tumours, one of three hepatocellular carcinomas, and five of eight metastatic tumours. The three adenomas identified on brush cytology could not be distinguished from adenocarcinoma morphologically. One hundred and sixty patients (39.4%) had benign strictures, most often as a result of chronic pancreatitis and bile duct stones. There were three false positive cytological diagnoses mainly as a result of the misinterpretation of cases with relatively scant and/or degenerative atypical epithelial cells. Forty one cases were reported as atypical or suspicious of malignancy on brush cytology, of which 29 were ultimately shown to have carcinoma. The overall diagnostic sensitivity and specificity were 59.8% and 98.1%, respectively. The sensitivity increased from 44.3% in the initial third of cases to 70.7% in the final third of cases examined in the series. Conclusions —Brush cytology, in conjunction with other clinical and radiological investigations, is a useful technique in the assessment of patients with suspected pancreatico–biliary neoplasia.